Analisis Pengaruh Citra Destinasi, Preferensi Wisatawan dan Kualitas Pelayanan terhadap Keputusan Berkunjung di Istana Maimoon Medan - Maria Magdalena Sihotang; Kustoro Budiarta (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to analyze the influence of Destination Image, Tourist Preferences, and Service Quality on the Decision to Visit Istana Maimoon Medan. The research method employed is a quantitative approach. The population of this study is all visitors of Istana Maimoon, with a sample size of 160 respondents taken using purposive sampling. Data analysis used is Path Analysis. Data collection was done using a questionnaire. The results of this study show that hypotheses 1-7 are accepted, namely: (1) Destination Image has a positive and significant effect on Service Quality, (2) Destination Image has a positive and significant effect on the Decision to Visit, (3) Tourist Preferences have a positive and significant effect on Service Quality, (4) Tourist Preferences have a positive and significant effect on the Decision to Visit, (5) Service Quality has a positive and significant effect on the Decision to Visit, (6) Service Quality mediates the influence of Destination Image on the Decision to Visit, and (7) Service Quality mediates the influence of Tourist Preferences on the Decision to Visit. These findings provide important insights for destination managers to enhance their image and service quality to attract more tourists.